2017
DOI: 10.1515/biol-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

MiR-107 inhibits proliferation of lung cancer cells through regulating TP53 regulated inhibitor of apoptosis 1 (TRIAP1)

Abstract: Conclusions: MiR-107 suppresses cell proliferation by targeting TRIAP1 in lung cancer. Our finding allows new insights into the mechanisms of lung cancer that is mediated by miR-107.Keywords: miR-107, TRIAP1, proliferation, lung cancer IntroductionLung cancer is the principle cause of global cancerassociated mortality accounting for about 1.59 million deaths every year worldwide [1, 2]. Most of those cases have non-small-cell lung cancer (NSCLC) [3].MicroRNAs (miRNAs) usually negatively modulate gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Evidence has indicated that the expression of TRIAP1 mRNA correlates with myelomas and breast cancer [40, 41]. TRIAP1 is up-regulated in drug-resistant breast cancer cells, and regulates breast cancer cells’ sensitivity to doxorubicin [10, 39, 40]. In the present study, it was demonstrated that TRIAP1 is the direct target of miR-107.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Evidence has indicated that the expression of TRIAP1 mRNA correlates with myelomas and breast cancer [40, 41]. TRIAP1 is up-regulated in drug-resistant breast cancer cells, and regulates breast cancer cells’ sensitivity to doxorubicin [10, 39, 40]. In the present study, it was demonstrated that TRIAP1 is the direct target of miR-107.…”
Section: Discussionsupporting
confidence: 62%
“…Among them, over 200 have been identified in humans [9]. miRNAs can negatively modulate gene expression by targeting mRNAs and trigger either translation repression or RNA degradation [10, 11]. Normally, conserved miRNAs have critical functions across many processes, such as cell proliferation, apoptosis, and metabolism [12, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs regulate cell proliferation and apoptosis by targeting specific genes during cellular processes (22). According to previous studies, TRIAP1 was predicted to be a candidate oncogene in various types of cancer, including ovarian cancer (23), nasopharyngeal carcinoma (24) and lung cancer (25). In the present study, TRIAP1 was revealed to be upregulated in lung cancer tumor tissues compared with adjacent non-tumor tissue.…”
Section: Discussionsupporting
confidence: 53%
“…Functional Wound Closure miRNA-107 inhibits cell proliferation and migration. [24][25][26][27] Delivery of anti-miR-107 using a commercially available transfection reagent (Dharmafect1) accelerates keratinocyte proliferation and migration (Figures S2A and S2B). However, when anti-miR-107 was delivered using TLN k/anti-miR-107 , a marginal change in cell migration was observed, although cell proliferation was increased (Figures S3A and S3B).…”
Section: In Vivo Targeting Efficiency Of Tln Kmentioning
confidence: 99%